The effect of health-promoting lifestyle education on the treatment of unexplained female infertility. (December 2016) - Kaya, Yeliz; Kizilkaya Beji, Nezihe; Aydin, Yunus; Hassa, Hikmet
Abstract: Objective: This study aimed to reveal the 1) awareness, 2) improvements of a health-promoting lifestyle on women with unexplained infertility having at least one of the risk factors that have been indicated to negatively affect fertility (smoking, body mass index lower than 18.5 kg/m 2 and more than 25 kg/m 2, over-exercising or not exercising at all, alcohol consumption, caffeine consumption of more than 300 mg/day, and high levels of stress) by means of health-promoting lifestyle education, 3) the effect of this improvement on the result of assisted-reproduction treatment in terms of clinical pregnancy. Study design: 64 women diagnosed with unexplained infertility were divided into a group receiving Health-Promoting Lifestyle (HPL) education and a control group. 1) Risk Factors Questionnaire (BMI, Smoking, Alcohol, Stress, Exercise, Caffeine), 2) Depression, Anxiety and Stress Scale, 3) Health-Promoting Lifestyle Profile II. The health promoting lifestyle was given to the education group. The Risk Factors Questionnaire; Depression, Anxiety, Stress Scale and Healthcare-Promoting Lifestyle Profile II were also administered after the first-second-third month of education but before ART treatment. Results: A statistically significant decrease was found in the average levels of four variables as; BMI (p < 0.001)-stress (p < 0.001)-caffeine consumption (p < 0.001)-lower exercise levels (p < 0.001). Moreover, the total number of risk factors that females had between the first and third interview decreased significantly. Clinical pregnancy rate after ART was 12 (46.1%) and 5 (19.2%) in education and control group consequently (p = 0.02). Conclusion: Health-promoting lifestyle education was found to be effective in reducing the lifestyle risk factors for infertility and increasing the success rates of assisted reproduction treatment by correcting these risk factors.